Low Level Light Therapy Modulates Inflammatory Mediators Secreted by Human Annulus Fibrosus Cells during Intervertebral Disc Degeneration In Vitro. (26th January 2015) - Hwang, Min Ho; Shin, Jae Hee; Kim, Kyoung Soo; Yoo, Chang Min; Jo, Ga Eun; Kim, Joo Han; Choi, Hyuk
Abstract Intervertebral disc degeneration (IVD) is one of the important causes of low back pain and is associated with inflammation induced by interaction between macrophages and the human annulus fibrosus (AF) cells. Low‐level light therapy (LLLT) has been widely known to regulate inflammatory reaction. However, the effect of LLLT on macrophage‐mediated inflammation in the AF cells has not been studied till date. The aim of this study is to mimic the inflammatory microenvironment and to investigate the anti‐inflammatory effect of LLLT at a range of wavelengths (405, 532 and 650 nm) on the AF treated with macrophage‐like THP‐1 cells conditioned medium (MCM) containing proinflammatory cytokines and chemokines (interleukin‐1beta, tumor necrosis factor‐alpha, interleukin‐6 and 8). We observed that AF cells exposed to MCM secrete significantly higher concentrations of IL‐6, IL‐8, IL‐1β and TNF‐α. LLLT markedly inhibited secretion of IL‐6 at 405 nm in a time‐dependent manner. Level of IL‐8 was significantly decreased at all wavelengths in a time‐dependent manner. We showed that MCM can induce the inflammatory microenvironment in AF cells and LLLT selectively suppressed IL‐6 and 8 levels. The results indicate that LLLT is a potential method of IVD treatment and provide insights into further investigation of its anti‐inflammation effect on IVD.